PEMURNIAN CNT (CARBON NANOTUBE) HASIL SPRAY-PYROLISIS DENGAN OPTIMASI PERLAKUAN WAKTU REFLUKS DAN APLIKASINYA UNTUK ADSORPSI KLOROFOM - Setyaningsih, Yeni (Chem Info Journal, 2013)
Purification of carbon nanotubes has been carried out by the method of synthesis results using spray-pyrolisis reflux treatment by reacting carbon nanotubes with nitric acid (HNO3) and its application for the adsorption of chloroform. Reflux is done by the time variation of 1, 2, 3, 4, and 5 hours. Carbon nanotube (CNT) synthesis results and the results of reflux were analyzed using SEM (Scanning Electron Microscopy) and EDS (Energy dispersive X-ray Spectroscopy), and then applied to adsorption of chloroform. The results show that Fe impurities in carbon nanotubes decreases with increasing reflux time, while the adsorption capacity increased with increasing reflux time. Purity carbon nanotubes are the best in the carbon nanotube that reflux for 5 hours, while the ability of chloroform adsorption maximum of 5.8217 x10-4 g / mol to the carbon nanotube in which at reflux for 5 hours.